Magnetic nanoparticle (MNPS) for removal of dyes in aqueous solution - Azman, I’rfan Akmal (2023)
Methylene blue solution is a thiazine dye that is commonly used in medicine, textile, paper and other industries. When methylene blue is irresponsibly deposited in water bodies, the dye can act as a contaminant as small concentrations are able to cause surface water to be cloudy, decreasing ability of aquatic plants to photosynthesize due to limited sunlight. This will eventually affect the entire aquatic ecosystem from disruption of producers in the food chain. For humans, contamination of methylene blue stems from its carcinogenic properties but can also cause in cyanosis, shock, gastritis, jaundice, methemoglobinemia, tissue necrosis, elevated heart rate, premature cell death in tissues, and irritation of the skin and eyes. Thus, functionalized magnetic nanoparticle with thymol (MNP@thymol) and menthol (MNP@menthol), was synthesised to filter methylene blue solution via coprecipitation method. Research also aimed to characterized MNPs, conduct batch adsorption study for three factors and tested for two adsorption isotherms. Results showed synthesised MNPs that were characterized by Fourier Transform Infrared Spectroscopy (FTIR). exhibited presence of hydroxyl group detected at 3350 cm⁻¹ to prove functionalization of MNP to thymol and bands at 3510 cm⁻¹ to prove functionalization of MNP to menthol. Then, batch adsorption study was carried out for pH, contact time and dosage. Optimum conditions for MNP@thymol were dosage of (0.5g), pH5 and contact time of 60 minutes while MNP@menthols’ were dosage (0.5g), pH8 and contact time of 60 minutes. Functionalized MNPs both suited the Langmuir adsorption isotherm.